Can coastline plant species be used as biosamplers of emerging contaminants? - UV-filters and synthetic musks as case studies - H. Ribeiro (2017)
Personal care products, an important class of emerging contaminants, have been frequently detected in different environmental matrices. Included in this category are synthetic musks compounds (SMCs) and UV-filters. Their occurrence in the coastal environment has been poorly studied. Therefore, this work aimed to verify whether five coastline plant species (Carpobrotus edulis, Cakile maritima, Medicago marina, Elymus farctus borealis-atlanticus and Euphorbia paralias) have the ability to accumulate 11 SMCs (cashmeran, celestolide, phantolide, galaxolide, tonalide, exaltolide, musk moskene, tibetene, ambrette, xylene and ketone) and 2 organic UVB filters (3-(40 -methylbenzylidene) camphor and octocrylene), functioning as biosamplers. To accomplish this task, a QuEChERS technique ("Quick, Easy, Cheap, Effective, Rugged, and Safe") was employed to extract the target compounds from the plant material collected in 15 beaches of Matosinhos and Vila Nova de Gaia (Portugal). The resulting extracts were analysed by gas chromatographyemass spectrometry. Limits of detection ranged from 0.02 ng g1 for celestolide and tonalide to 1.32 ng g1 for musk ambrette. The obtained recoveries were around 93% and relative standard deviation was generally less than 15%. SMCs were detected at levels ranging from 1.56 to 350 ng g1 dw and UV-filters from 2.9 to 264 ng g1 dw. Galaxolide and 3-(40 -methylbenzylidene) camphor were the synthetic musk and UV-filter detected in higher concentrations, respectively. Plants with higher water content accumulate better SMCs (hottentot-fig), while those with higher lipid content retain better the UV-filters (sea spurge).